(untitled) (Bangladesh Journal of Medical Microbiology, 2023)
Background: COVID-19 disease is a varied epidemiological aspect. Objectives: The aim of the study was to assess the epidemiological aspects and demographic factors responsible for COVID-19 Infection at Manikganj district of Bangladesh. Methodology: This descriptive cross-sectional study was conducted in the Department of Microbiology at Colonel Malek Medical College, Manikganj, Bangladesh from November 2020 to June 2021 for a period of eight months. The suspected cases of covid-19 patients or patients who had the history of contact with the confirmed cases of Covid-19 cases were advised by the clinician to do the test confirmatory test. RT-PCR for COVID-19 test was performed and results were recorded with their age, gender as well as the details history of the patients. Results: A total number of 6678 cases were recruited for this study. The relationship between the urban and rural positivity of COVID-19 cases were statistically significant (p=0.000). Travel history was important factor for positivity among the COVID-19 patients. However, out of 675 cases of having history of travel COVID-19 was positive in 43(6.4%) cases. Again, 6003 patients were without travel history and among these 625(10.4%) cases were COVID-19 RT-PCR positive. The association between the travel history with the positivity of COVID-19 cases were statistically significant different (p=0.001). Among all Upazila Singair was the highest reported COVID-19 cases during the study period which was 356 cases followed by Shibalaya and Saturia which was 277 cases and 265 cases respectively. There was a significant association of COVID-19 positive cases and the different Upazila of Manikganj was found (p=0.000). Conclusion: In conclusion few upazila of manikganj district are affected with COVID-19 with the history of travel. Bangladesh Journal of Medical Microbiology, July 2022;16(2):38-46